Answer: 32
Step-by-step explanation:
The only point in the solution space is that of selection ...
C (1, 3)
Y=(-x*x)-4x+3
y=-(x^2+4x-3)
4+y=-(x^2+4x+4)+3
y+4=-(x-2)^2.) +3
-4. -4
y=-((x-2)^2)-1
Answers:
Vertex: (2,-1)
AOS:x = 2
Domain: All Real Numbers
Range:[-1,Infinity)
Answer:
<h2>6</h2>
Step-by-step explanation:
<h3>to understand this</h3><h3>you need to know about:</h3>
<h3>given:</h3>
<h3>let's solve:</h3>
- substitute the value of y:2²-2.2+6
- simplify exponent:4-2.2+6
- simplify multiplication;4-4+6
- simplify addition:4+2
- simplify addition:6
The answer is 20
Hope this helps